2014
DOI: 10.3390/ijerph110606136
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Epidemiology and Preventive Healthcare in Multiethnic Societies: The Hemoglobinopathies

Abstract: Healthy carriers of severe Hemoglobinopathies are usually asymptomatic and only efficiently detected through screening campaigns. Based upon epidemiological data, screenings have been offered for decades to populations of endemic Southern Europe for primary prevention of Thalassemia Major, while for many populations of the highly endemic African and Asian countries prevention for Sickle Cell Disease and Thalassemia Major is mainly unavailable. The massive migrations of the last decades have brought many health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…(14) Identification of carriers is also offered early in pregnancy in most developed countries due to high migration rates of populations from high thalassemia prevalence areas to West European countries. (16) Undoubtedly these studies have shown that thalassemia prevention programs including premarital and prenatal screening have been cost-effective in reducing the thalassemia prevalence. (17) One should bear in mind that it is of utmost importance to dispel the misconception about thalassemia carriers, so that this genetic disorder is not stigmatized by society.…”
Section: Discussionmentioning
confidence: 99%
“…(14) Identification of carriers is also offered early in pregnancy in most developed countries due to high migration rates of populations from high thalassemia prevalence areas to West European countries. (16) Undoubtedly these studies have shown that thalassemia prevention programs including premarital and prenatal screening have been cost-effective in reducing the thalassemia prevalence. (17) One should bear in mind that it is of utmost importance to dispel the misconception about thalassemia carriers, so that this genetic disorder is not stigmatized by society.…”
Section: Discussionmentioning
confidence: 99%
“…However, demographic events, such as migration from high-prevalence areas and the consequent intermixing of populations, have contributed to the spread of haemoglobinopathies worldwide [68] and, consequently, their prevalence is rising in non-endemic regions, such as Northern and Western Europe and North America, posing a major challenge for researchers and health professionals. In addition, the lack of high-quality epidemiological data, the high variation of disease prevalence in different ethnic groups and in different regions within the same country, as well as general underestimates of haemoglobinopathy incidence, particularly in low-and middle-income countries, are serious impediments to appropriate policy making [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These limitations do not apply to population screening and premarital screening has successfully reduced births with beta thalassaemia in Cyprus (Angastiniotis and Hadjiminas 1981) and Sardinia (Cao et al 1996) and has led to mandatory premarital screening in Iran (Karimi et al 2007), Bahrain (Al Arrayed 2005b), Saudi Arabia (Al Hamdan et al 2007), the Palestinian territories (Tarazi et al 2007), and Cyprus (Cowan 2009) as reviewed by Giordano et al (2014). Although contrary to the WHO guidelines (WHO 1998) on compulsory genetic testing, these programmes seem to have been well accepted.…”
Section: Discussionmentioning
confidence: 99%